Rodent group borreliae do occur in wild rodents from the Caribbean region of Colombia (2024)
Background: Bacteria of the genus Borrelia are agents of disease in both domestic animals and humans and pose a significant public health risk. Borrelia species have complex transmission cycles, often using rodents as vertebrate reservoir hosts. These bacteria are classified into three well-defined monophyletic groups: Borrelia burgdorferi sensu lato (Bbsl) complex, the relapsing fever (RF) group, and a third group associated with reptiles and echidnas. Moreover, a new group of Borrelia associated with rodents has recently been proposed, as these bacteria form a phylogenetic group separated from the previously mentioned groups. This study aimed to investigate the presence of DNA of Borrelia spirochetes in rodents in specific areas of the Colombian Caribbean. Methods: A total of 155 rodent spleen samples were selected from the tissue bank. These samples were obtained in the departments of La Guajira and Córdoba (Northern Colombia). DNA extraction and specific real-time polymerase chain reaction (PCR) targeting Borrelia 16S ribosomal RNA (rRNA) gene were performed, followed by nested PCR (nPCR) on positive samples to obtain larger fragments of the 16S rRNA gene and characterize the flaB gene. Alignments of generated sequences and ortholog sequences downloaded from Genbank were performed in Clustal Omega. A phylogenetic tree was built with the maximum likelihood method in IQTREE. Results:Spleen samples from rodents of the genera Heteromys, Mus, Necromys, Olygoryzomys, Proechymis, Rattus, Sigmodon, and Zygodontomys were processed. Overall, 6.5% (4/162) of the animals tested positive for Borrelia by real-time PCR. All quantitative PCR (qPCR)-positive samples were also positive for nPCR targeting the 16S rRNA gene, yielding fragments of 344–408 bp and 603–673 bp from two Sigmodon rodents and two Zygodontomys rodents from La Guajira and Córdoba. All samples were negative for the flaB gene. Only samples from Zygodontomys rodents presented good quality sequences. A BLASTn analysis showed a percentage of identity ranging between 98.16 and 96.06% with Borrelia sp. R57. Phylogenetic analysis revealed that sequences of the present study clustered with species of the recently proposed Borrelia “rodent group.” Conclusions: This is the first detection of borreliae of the “rodent group” in South America. Our results reaffirm the occurrence of a group of spirochetes associated with rodents, extending its geographic distribution to the Colombian Caribbean.